2016
DOI: 10.5812/ijp.3621
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Results of Device Occlusion of Patent Ductus Arteriosus

Abstract: BackgroundTranscatheter patent ductus arteriosus (PDA) closure is an established procedure.ObjectivesThe aim of the study was to assess midterm follow up of the Nit-Occlud coil and the amplatzer ductal occluder (ADO) closure of PDA.Patients and MethodsIn this cohort study, we collected the longitudinal data of patients who underwent percutaneous closure using coil or ADO from November 2005 to November 2013. A total of 404 patients with PDA closure by devices were included during the study period. Coil occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
5
17
1
Order By: Relevance
“…The LVESD also showed a significant decrease immediately after PDA closure and continued to decrease at the onemonth follow up, but non significantly. These findings are concordant with the previous study conducted by Gupta et al (6) which showed a significant decrease of the LVESD at day-1 and at the short term follow up after PDA closure (11) . The decrease in LVESD in the short term follow up in our study was concordant with previous studies conducted by Amoogzar et al (11) , Galal et al (12) and Kim et al (5) .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The LVESD also showed a significant decrease immediately after PDA closure and continued to decrease at the onemonth follow up, but non significantly. These findings are concordant with the previous study conducted by Gupta et al (6) which showed a significant decrease of the LVESD at day-1 and at the short term follow up after PDA closure (11) . The decrease in LVESD in the short term follow up in our study was concordant with previous studies conducted by Amoogzar et al (11) , Galal et al (12) and Kim et al (5) .…”
Section: Discussionsupporting
confidence: 93%
“…As regards the LV dimensions, the LVEDD showed a significant decrease in the mean LVEDD and the mean LVEDD indexed to BSA immediately after successful PDA closure and continued to decrease in the one month follow up after closure but non significantly. These findings are concordant with the studies conducted by Amoogzar et al (11) ; Agha et al (7) ; Galal et al (12) ; Kim et al (5) and Gupta et al (6) . These studies reported that LVEDD decreases significantly after PDA closure and continues to decrease further at the onemonth follow up and after longer periods of follow up, up to six months, in some of these studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Amoozgar et al reported 97.8% success rate with ADO device closure. 6 Sultan et al implanted PDA successfully in 98.2% patients. 12 In USA the reported success rate after ADO device closure is 99%.…”
Section: Variables Valuementioning
confidence: 99%